Developmental programming: Prenatal testosterone excess disrupts pancreatic islet developmental trajectory in female sheep. (1st December 2020) - Jackson, Ian J.; Puttabyatappa, Muraly; Anderson, Miranda; Muralidharan, Meha; Veiga-Lopez, Almudena; Gregg, Brigid; Limesand, Sean; Padmanabhan, Vasantha
Abstract: Prenatal testosterone (T)- treated female sheep manifest juvenile insulin resistance, post-pubertal increase in insulin sensitivity and return to insulin resistance during adulthood. Since compensatory hyperinsulinemia is associated with insulin resistance, altered pancreatic islet ontogeny may contribute towards metabolic defects. To test this, pregnant sheep were treated with or without T propionate from days 30–90 of gestation and pancreas collected from female fetuses at gestational day 90 and female offspring at 21 months-of-age. Uterine (maternal) and umbilical (fetal) arterial blood insulin/glucose ratios were determined at gestational day 90. The morphological and functional changes in pancreatic islet were assessed through detection of 1) islet hormones (insulin, glucagon) and apoptotic beta cells at fetal day 90 and 2) islet hormones (insulin, glucagon and somatostatin), and pancreatic lipid and collagen accumulation in adults. At gestational day 90, T-treatment led to maternal but not fetal hyperinsulinemia, decrease in pancreatic/fetal weight ratio and alpha cells, and a trend for increase in beta cell apoptosis in fetal pancreas. Adult prenatal T-treated female sheep manifested 1) significant increase in beta cell size and a tendency for increase in insulin and somatostatin stained area and proportion of beta cells in the islet; and 2) significant increase in pancreatic islet collagen and a tendency towards increased lipid accumulation. Gestational T-treatment induced changes in pancreatic islet endocrine cells during both fetal and adult ages track the trajectory of hyperinsulinemic status with the increase in adult pancreatic collagen accumulation indicative of impending beta cell failure with chronic insulin resistance. Graphical abstract: Image 1 Highlights: Gestational T excess induces maternal but not fetal hyperinsulinemia. Gestational T excess reduced pancreatic/fetal weight ratio and fetal islet α cells. Prenatal T-excess increased β cell size and collagen content. Prenatal T excess tended to increase β cell number islet insulin and lipid content. Prenatal T excess-induced islet disruptions contribute to hyperinsulinemia.